A Substantive Justice-Based Model for Controlling Judicial Discretion in the Application of Judicial Pardon - Rianda Prahartiwi; Kadi Sukarna (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines the problem of judicial discretion in the application of judicial pardon under Article 54 paragraph (2) of Law Number 1 of 2023 concerning the Indonesian Criminal Code (KUHP). Judicial pardon represents a significant reform in the sentencing system, as it allows judges to refrain from imposing criminal sanctions or measures even when the defendant has been proven guilty. However, the formulation of the provision contains broad and open-ended phrases such as “the minor nature of the offense,” “the personal circumstances of the offender,” “justice,” and “humanity,” which may give rise to subjectivity, sentencing disparities, and legal uncertainty if not accompanied by adequate control parameters. This study employs a normative-prescriptive legal research method using statutory, conceptual, and limited comparative approaches. The findings indicate that the application of judicial pardon should be guided by a substantive justice-based model encompassing four control mechanisms: proof of culpability, eligibility for pardon, consideration of the interests of victims and society, and explicit as well as reviewable legal reasoning. This model positions judicial pardon not as an act of subjective leniency, but as a rational, proportional, and accountable judicial mechanism.